2014
DOI: 10.12973/eurasia.2014.1220a
|View full text |Cite
|
Sign up to set email alerts
|

College Students Attitude and Mathematics Achievement Using Web Based Homework

Abstract: The goal of this study was to understand how students' attitudes were connected to their mathematics learning and achievement. This investigation of students (n = 78) and their attitudes was specific to web-based homework in developmental mathematics courses in a two-year community college located in a large urban city in the United States. A mixedmethods investigation was utilized to analyze the relationships between students' attitudes and their mathematics achievement. The qualitative findings from the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
0
11
0
2
Order By: Relevance
“…Previous research also indicates that students are more motivated to complete online homework than paper-based homework [20]. Furthermore, several studies on the acceptance of online homework have shown that students appreciate online homework in mathematics courses [9, p. 2], [17], [21]- [23].…”
Section: Review Of Researchmentioning
confidence: 99%
“…Previous research also indicates that students are more motivated to complete online homework than paper-based homework [20]. Furthermore, several studies on the acceptance of online homework have shown that students appreciate online homework in mathematics courses [9, p. 2], [17], [21]- [23].…”
Section: Review Of Researchmentioning
confidence: 99%
“…A series of research on the influence of web-based tools and computer simulations used in classroom work and homework prove their efficiency (Jacobson, 2006;Campbell et al, 2010;Wooten & Eggers, 2013;Leong & Alexander, 2014;Wang et al, 2014). Moreover, this positive effect is stable and lasts for over 10 years.…”
Section: Analysis Of International Studiesmentioning
confidence: 98%
“…The second strand of related research addresses pedagogy in college mathematics (e.g., Elrod & Strayer, 2018;Hauk & Segalla, 2005;Leong & Alexander, 2014). More specifically, technology-based mathematics learning has been championed as the solution to higher education's mathematics problem for numerous reasons such as giving just-in-time responses to students so that they can correct mathematical errors on the spot (Twigg, 2011).…”
Section: Related Researchmentioning
confidence: 99%